Pengaruh Penggunaan Media Diorama Siklus Air terhadap Pemahaman Konsep IPA Siswa Kelas V UPTD SD Negeri 3 Parepare - Anugrah Sri Pebrianti; Nurul Mukhlisa; Ila Israwaty (MASALIQ, 2026)
Elementary school students’ understanding of Natural Sciences (IPA) concepts, particularly the water cycle, remains relatively low because of the abstract nature of the material and instruction dominated by textbook use. This condition indicates the need for instructional media capable of visualizing concepts concretely so that the material can be understood more easily. This study aims to analyze the effect of using water cycle diorama media on the understanding of IPA concepts among fifth-grade students at UPTD SD Negeri 3 Parepare. The study employed a quantitative approach with a quasi-experimental research design using a Pretest–Posttest Control Group Design. The research population comprised all 594 students at UPTD SD Negeri 3 Parepare, while the sample consisted of 58 students divided into an experimental class of 30 Grade V.1 students and a control class of 28 Grade V.2 students. Data were collected using a 20-item multiple-choice test administered before (pretest) and after (posttest) the treatment and were subsequently analyzed using descriptive and inferential statistics. The results showed that the experimental class obtained a mean conceptual understanding score of 83.33, which was higher than the control class mean score of 66.79. The independent-samples t-test yielded a significance value of 0.001 < 0.05. These findings indicate that the use of water cycle diorama media had a significant effect on the understanding of IPA concepts among fifth-grade students at UPTD SD Negeri 3 Parepare. This study provides the practical implication that diorama media can be used as an alternative concrete instructional medium to help students visualize and understand the water cycle concept in elementary school IPA learning.